Structural elucidation of transmembrane domain zero (TMD0) of EcdL: A multidrug resistance-associated protein (MRP) family of ATP-binding cassette transporter protein revealed by atomistic simulation. Issue 11 (18th August 2018) - Bera, Krishnendu; Rani, Priyanka; Kishor, Gaurav; Agarwal, Shikha; Kumar, Antresh; Singh, Durg Vijay
Abstract : ATP-Binding cassette (ABC) transporters play an extensive role in the translocation of diverse sets of biologically important molecules across membrane. EchnocandinB (antifungal) and EcdL protein of Aspergillus rugulosus are encoded by the same cluster of genes. Co-expression of EcdL and echinocandinB reflects tightly linked biological functions. EcdL belongs to Multidrug Resistance associated Protein (MRP) subfamily of ABC transporters with an extra transmembrane domain zero (TMD0). Complete structure of MRP subfamily comprising of TMD0 domain, at atomic resolution is not known. We hypothesized that the transportation of echonocandinB is mediated via EcdL protein. Henceforth, it is pertinent to know the topological arrangement of TMD0, with other domains of protein and its possible role in transportation of echinocandinB. Absence of effective template for TMD0 domain lead us to model by I-TASSER, further structure has been refined by multiple template modelling using homologous templates of remaining domains (TMD1, NBD1, TMD2, NBD2). The modelled structure has been validated for packing, folding and stereochemical properties. MD simulation for 0.1 μs has been carried out in the biphasic environment for refinement of modelled protein. Non-redundant structures have been excavated by clustering of MD trajectory. The structural alignment of modelled structure has shown Z-score -37.9; 31.6, 31.5 with RMSD; 2.4, 4.2, 4.8 with ABC transporters; PDB ID 4F4C, 4M1 M, 4M2T, respectively, reflecting the correctness of structure. EchinocandinB has been docked to the modelled as well as to the clustered structures, which reveals interaction of echinocandinB with TMD0 and other TM helices in the translocation path build of TMDs.